Comparative Political Marketing pada Pemilihan Kepala Daerah Kota Tanjungpinang Tahun 2024 - Siti Nur Haliza; Bismar Arianto; Rizky Octa Putri Charin (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
In the 2024 Tanjungpinang City Pilkada, the Rahma-Rizha pair competed with Lis-Raja in the mayoral and deputy mayoral elections. Both candidate pairs have previous mayoral experience. The campaign was conducted directly to the public and utilized digital media. This study aims to compare the political marketing process between the Rahma-Rizha and Lis-Raja candidate pairs with the 4P theory by Philip B. Neffinegger and using qualitative methods. Based on the results of the product indicator study, the Lis-Raja pair excelled in active campaign programs and approaches, while Rahma-Rizha relied on the incumbent's experience and specific religious programs. Although their strategy was less than optimal, the program was an advantage over their political opponents. The promotion indicator showed the Lis-Raja pair's superiority in campaign effectiveness through social media and community support, while the Rahma-Rizha pair was stronger in direct meetings although less optimal in digital promotion and involvement of supporting figures. The price indicator explained that the Lis-Raja pair had greater financial capacity than the Rahma-Rizha pair. Finally, the place indicator shows that the Lis-Raja pair was more effective in approaching the community by involving religious figures as an effort to strengthen the religious brand by changing their appearance as a religious figure in the public eye, while Rahma tried to improve her image and support through Rizha, who has a background in preaching, to strengthen the mass base among religious figures, but this did not achieve the expected results. Although the Lis-Raja pair has an advantage in several political marketing indicators, such as a more active campaign program and effective use of social media, the Rahma-Rizha pair still has the potential to gain support, especially among voters who prioritize experience and personal strength in leadership.